Characterization of robust alignment mark to improve alignment performance - Normah, Ahmad; Uda, Hashim; Mohd Jefrey, Manaf; Kader, Ibrahim (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org